HIF-1α mediates Hypoxia-induced epithelial–mesenchymal transition in peritoneal mesothelial cells. (7th February 2016) - Morishita, Yoshiyuki; Ookawara, Susumu; Hirahara, Ichiro; Muto, Shigeaki; Nagata, Daisuke
Abstract: The epithelial-to-mesenchymal transition (EMT) of peritoneal mesothelial cells plays a pivotal role in the development of peritoneal fibrosis. The pathological effects of hypoxia on mesothelial cell EMT have not been fully elucidated. In this study, we, therefore, investigated the effects of hypoxia on EMT in mesothelial cells. Human mesothelial (MeT-5A) cells and primary-cultured rat mesothelial cells were cultured under hypoxic conditions (1% O2 ) for up to 72 h. Changes in cell type were then determined by investigating changes in morphology and in expression of epithelial (E-cadherin and occludin) and mesenchymal (fibronectin-1, vimentin and α-smooth muscle actin) cell markers. In some cases, MeT-5A cells were cultured under hypoxic conditions with a HIF-1α inhibitor and then assessed for changes in morphology and for altered expression of signaling molecules, such as HIF-1α, Snail-1, vascular endothelial growth factor (VEGF), and matrix metalloproteinase-2 (MMP-2). Levels of HIF-1α, Snail-1, VEGF, and MMP-2 in Met-5A cells were increased by hypoxia. Levels of epithelial cell markers were decreased and those of mesenchymal cell markers were increased. Cell morphology also changed from a cobblestone-like monolayer to spindle-shaped fibroblast-like cells in response to hypoxia. Inhibition of HIF-1α signaling by a HIF-1α inhibitor abrogated these changes. The cell marker and morphological changes induced by hypoxia were also observed in primary-cultured rat mesothelial cells. We can conclude that hypoxia induces EMT in mesothelial cells by activating HIF-1α. This finding indicates that hypoxia has pivotal roles in the development of peritoneal fibrosis in peritoneal dialysis patients.